Application of Head Elevation on Intracarnial Pressure in Stroke Patients - Kiswanto, Logi; Yamin, M.; Hidayat, Aris Teguh (JOSING: Journal of Nursing and Health, 2022)
This study aims to determine the effectiveness of applying head elevation to intracranial pressure in stroke patients. This research method uses one data, namely a literature study. The results showed that head elevations of 0°, 15°, 30°, and 45° affected intracranial pressure in stroke patients. In conclusion, it shows that 30° more head elevation can improve the intracranial pressure problem, although the difference's value is not significant. Keywords: Head Elevation, Intracranial Pressure, Stroke